0160 A bespoke mobile trolley maximises the benefits of in-situ simulation training to improve patient safety. (2nd November 2015) - Lane, Mary; Woods, James; Chamberlain, Latanya; Lofton, Lydia; Burmester, Margarita; White, Mary; Macgloin, Helen
Abstract : Background: The Simulated Interprofessional Team Training programme, SPRinT, a validated in-situ simulation programme delivers point-of-care team-training to >180 staff annually. In-situ simulation provides an authentic learning experience, key to translation into real clinical practice. Benefits include system testing and improvement, latent threat identification and mitigation, and team-work training of real teams. Description of innovation: To facilitate delivery of in-situ simulation throughout the hospital, (clinical areas in separate buildings), we decided to devise a mobile solution to minimise cost and set up time while maximising learning opportunities. Weinstock et al . 1 highlighted the usefulness of a self-contained mobile cart in their paediatric unit. We have thus developed the bespoke SPRinT trolley enabling delivery of in-situ simulations to multiple sites throughout the hospital. Trolley cost = £ 2250. The secure compact design maximises portability and equipment safety. It offers elevated monitor facilities and a lockable full size CPU cupboard with earth bonded power. Outcomes/improvements: Since introducing the SPRinT trolley, we have undertaken 95 SPRinT courses, training 711 members of hospital staff in 13 separate clinical locations including paediatric ICU/HDU/wards, adult ICU/HDU, outpatient clinics, theatres and recovery, catheter labs. 51 latent threats identified, resulting in 36 system quality improvements, 7 translated trust wide. Courses rated highly effective by >80% of participants. Take home message: Using the SPRinT trolley, we have delivered the benefits of in-situ simulation-based team-training to more areas and staff than traditional simulation centre model oftraining, improving team performance and patient safety. Our trolley is cost effective, half We in stock trolley cost. Availability of new wireless manikins means some of our trolley features are being redesigned to keep pace with this innovative technology. The newly designed trolley aims to be reproducible and cost effective so that all hospitals will be able to transform their delivery of simulation based education and training. Reference: Weinstock PH, et al . Simulation at the point of care: reduced-cost, in situ training via a mobile cart. Pediatr Crit Care Med. 2009;10(2):176–181